A study on performance of commercial bank using financial ratio / Nur Fathanah Kamis - Kamis, Nur Fathanah (2008)
Commercial banks are the largest and most important group of financial institution in Malaysia. However, the banks performance is differ from one and another. In order to know the performance, one of the best tools that can be use is financial ratio. This paper seeks empirical evidence on how the local and international commercial bank in Malaysia performs by using financial ratio. This study used three major financial ratio tools likes profitability, liquidity and credit risk ratio to look the each performance of commercial banks which had selected. Moreover, this study also used cross sectional analysis to make comparison each of banks selected. The banks that selected are Malayan Banking Berhad (MAY BANK), Hong Leong Bank Berhad, Standard Chartered Bank Malaysia Berhad and HSBC Bank Malaysia Berhad. The finding found that HSBC Bank was giving the good performance among others three banks for the period of five years. Second best performance was Standard Chartered Bank and followed by MAYBANK. Hong Leong Bank in the last places based on the profitability, liquidity and credit risk ratio.